Analisis Kesalahan Penggunaan Sintaksis Pada Koran Elektronik: Sinar Indonesia Baru Edisi April 2024 - Erfriani Sekar Talenta Simangunsong; Kristin Dwi Amsari Pasaribu; Jesicha Nainggolan; Erfanintiya Siringoring; Yuliza Rahma Lubis; Mustika Wati Siregar6 (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The research carried out is useful for analyzing errors in the use of syntax found in the electronic newspaper studied, namely "Sinar Indonesia Baru" 2024 edition. Syntax is a science that discusses grammar by identifying errors in words, sentences, clauses and phrases. For the public, electronic newspapers are an important medium because they contain a lot of information. However, as wise citizens, we must also ensure the clarity or truth of the information contained in electronic newspapers. In this case, the method or method used is to collect data and analyze errors in the electronic newspapers studied. The results of this research are to discuss errors such as grammar, unclear sentences, and errors in the contents of the newspapers analyzed. Therefore, this research functions as a provider of new insights for newspaper writers in order to improve the quality of the writer's writing and the quality of the language, especially in the April 2024 edition of the electronic newspaper "Sinar Indonesia Baru".